Pemodelan Ruang Terbuka Hijau untuk Reduksi CO2 di PT. Wilmar Nabati Gresik: Pendekatan SEM-PLS - Sutanto, Riki; Santoso, Irwan Bagyo (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2025)
One of Sustainable Development Goals related to climate change is reducing greenhouse gas emissions, namely carbon dioxide (CO2) from human activities. Properly designed green open spaces impact human health and the environment. PT Wilmar Nabati Gresik is a large palm oil producer that produces emissions from the industrial sector. This study aimed to determine the value of ambient air CO2 absorption by green open spaces and its modeling at PT. Wilmar Nabati Gresik. Observations and measurements of ambient CO2 air samples were carried out every 1 hour for 24 hours in 6 days using a CO2 meter. Furthermore, the measurement results were analyzed using SEM-PLS to explore the correlation between variables and their indicators. The cumulative value of carbon dioxide (CO2) in ambient air or Net CO2 is used as an indicator of the amount of carbon dioxide reduction. The three latent variables of this study are CO2 concentration (C), plants (T) and land use (A). The indicators of this study are the minimum CO2 concentration (Cmin), maximum (Cmax), average (Cavg), percentage of tree vegetation, shrubs, grass, percentage of jetty land, office, plant and non-RTH land. The results showed the average CO2 concentration of ambient air in 6 days at PT. Wilmar Nabati Gresik was 521 ppm. Vegetation is dominated by trees and grass, and the smallest proportion of land and vegetation is plant clusters. Furthermore, a mathematical model was made for planning green open space vegetation. It was concluded that additional green open space is needed at PT. Wilmar Nabati Gresik by planting trees coverage of 2.46 ha to reduce Net CO2 to 0. Keywords: air emissions, carbon dioxide, modelling, green open space